Exposure of remote maritime populations to coplanar PCBs. - Dewailly, E (1994)
Two remote maritime populations were evaluated for their biological exposure to organochlorines in 1989-1990. Because of their high intake of seafood, these two populations have high biological levels. One hundred nine breast milk samples from Inuit women from Arctic Québec were analyzed to determine levels of polychlorodibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and coplanar polychlorinated biphenyls (PCBs) including non-ortho, mono-ortho, and di-ortho congeners. Total 2,3,7,8-tetrachlorodibenzo-p-dioxin equivalents (TEqs) for PCBs were 3.5 times higher in Inuit milk samples than in 96 Caucasian milk samples. Among the 185 fishermen from the Lower North Shore of the Gulf of the St. Lawrence River, we evaluated 10 highly exposed fishermen for their coplanar PCB blood levels. Total TEqs were 900 ng/kg for highly exposed individuals with 36 ng/kg for controls. In these two nonoccupationally exposed populations, coplanar PCBs make a larger contribution to the TEq than PCDDs and PCDFs. However, the mono-ortho penta CB No. 118 is the major contributor for the total toxicity.